Marketing Communication on Facebook Pages: How Are Facebook Pages Facilitating Marketing Communications? - Khin, Aung Chit (2009)
Marketing communications have been focusing mostly on what the companies tell the customers. Now, social media and Facebook Pages have offered organizations to talk with their customers – pursue two-way dialogues. Anyone can set up and use the Pages free-of-charge but many pages have gathered up over millions of Fans forming into large virtual communities on various topics, personalities, brands and organizations. Facebook, leading the social media world with various features afforded by its open development platform, is the largest Social Networking Site (SNS) on the verge of achieving 300 million users. This study looked into the marketing communications opportunities offered by Facebook Pages addressing the research question ―how Facebook Pages facilitate marketing communications?‖ Netnography method was used to develop multiple cases. The findings revealed that official pages administered by the companies are using the pages for brand building, customer relationship marketing (CRM) and Fan relations, public relations, sales promotion, viral marketing and marketing research. The Fans‘ contents, UGCs were mostly general expression of love for the product/brand and falls into Andreassen and Streukens‘ (2009) meta-themes of eWOMs - business practice, usage experience and information requests and a product launches and developments. Unofficial Pages share the features of both Fans and official Page administrators‘ contents. The findings suggest that most of the contents on the pages are not engaged dialogues but mere ―monologic dyads‖ (Varey, 2002). However, Fans do attempt to pursue deeper dialogues in certain circumstances. The Fans also expect the companies to understand and play by the social media rules. The study also reveal the implications on marketing communications: co-creation of messages, compromised control, dealing with multiple stakeholder groups, exposure to potential PR disasters and possible confusions for the positioning of localized global brands. This report recommends organizations to be prepared to engage in marketing conversations on-demand, to create regional Pages, offer viral marketing contents, and use the Pages for marketing research. The paper also suggests tactics to use the Pages as customer relationship marketing tool, Public relations tool as well as offer guidance in using Pages for branding and IMC drawing from the case studies. The study predicts a change of direction in marketing communications where corporations offer better transparency and pursue mass personal communications with their publics to achieve closer relationships and understanding enabled by the social media.